An educational game on the theories of driver education curriculum: An evaluation - Zainab Othman; Nurul Hidayah Mat Zain; Ismassabah Ismail; Sharifah Affandi; Nor Azida Mohamed Noh; Anita Mohd Yasin (Institute of Advanced Engineering and Science, 2020)
The purpose of this study was to evaluate the effectiveness of using an educational game application among driving school students on their understanding of driving rules and regulations. The application was developed and named as An Educational Game on the Theories of Driver Education Curriculum (DEC) to help students improve their visualization, understanding and memorization of the theories of driving rules and regulations as well as to be more prepared before taking the driving theory test. A preliminary study was conducted and it indicated that students had a hard time in visualizing, understanding and memorizing the theories of driving. The Game Development Life Cycle (GDLC) was implemented as a methodology to develop the DEC application which consists of initiation, pre-production, production, testing, beta, and release phases. The effectiveness of the DEC application was measured by Game-Based Learning Evaluation Model (GEM). The findings indicated that educational game helped students to visualize, memorize and understand the theories of driving easily.